OPPENHEIMER (2023) BIOPIC: PERFORMING ACTING OUT, SEEKING WORKING THROUGH - Sevtia Nanda; Uci Elly Kholidah; Zietha Arlamanda Asri (PARADIGM: Journal of Language and Literary Studies, 2026)
Mental health and trauma now dominate social discourse as well as contemporary cinema, reflecting a growing collective awareness of post-war historical wounds. This study examines the representation of J. Robert Oppenheimer’s traumatic experiences in the film Oppenheimer (2023) and assesses how that cinematic narrative aligns with selected biographical records. The analysis draws on Cathy Caruth’s concepts of belatedness and repetition compulsion and is complemented by Dominick LaCapra’s distinction between acting out and working through. Using a biographical approach, trauma-related moments identified in the film script are juxtaposed with historical documents in Robert Oppenheimer, Letters and Recollections. The findings identify 59 trauma-related instances: 32 cases (54%) reflect acting out, while 27 cases (46%) reflect working through. In the film, trauma is primarily conveyed through psychological disturbances and the intrusion of subconscious memories. In contrast, the biographical documents portray a more structured and sustained pattern of reconciliation, in which working through appears more dominant.